Gender Differences in Cardiovascular Pharmacotherapy—the Example of Hypertension: A Mini Review - Kalibala, Jacklean; Pechère-Bertschi, Antoinette; Desmeules, Jules (Frontiers in Pharmacology, 2020)
Cardiovascular disease (CVD) is the leading cause of mortality worldwide in both sexes. Despite considerable progress in better understanding the patterns of disease in women, they are still often undertreated and benefit less from evidence-based treatment. Hypertension is a key contributor to CVD and is also one of the most potent risk factors for heart failure in women. Even with the wide variety of available drugs, blood pressure control is globally suboptimal. Current guidelines do not suggest differential treatment of hypertension for women; however, a growing body of research suggests gender dimorphism in the pathophysiology of hypertension and pharmacological response to cardiovascular drugs. The clinical relevance of theses sex-divergent effects of drugs is still under investigation. Owing to the exponential relationship between blood pressure and cardiovascular mortality, even a modest decrease in blood pressure or therapeutic adhesion could be clinically elevant. In this review, we explore the known pharmacological and pharmacokinetic sex differences with special attention to the main classes of antihypertensive treatment. Current data shows frequently higher drug exposures in women and more frequent adverse drug reactions in all antihypertensive drug groups. As far as cardiovascular prevention is concerned, sex-specific data is often lacking in clinical trials, highlighting the necessity to further study CVD and their treatment in both men and women.